Adipose Gene Expression Profile Changes With Lung Allograft Reperfusion. Issue 1 (18th August 2016) - Diamond, J. M.; Arcasoy, S.; McDonnough, J. A.; Sonett, J. R.; Bacchetta, M.; D'Ovidio, F.; Cantu, E.; Bermudez, C. A.; McBurnie, A.; Rushefski, M.; Kalman, L. H.; Oyster, M.; et al.
Abstract : Obesity is a risk factor for primary graft dysfunction (PGD), a form of lung injury resulting from ischemia–reperfusion after lung transplantation, but the impact of ischemia–reperfusion on adipose tissue is unknown. We evaluated differential gene expression in thoracic visceral adipose tissue (VAT) before and after lung reperfusion. Total RNA was isolated from thoracic VAT sampled from six subjects enrolled in the Lung Transplant Body Composition study before and after allograft reperfusion and quantified using the Human Gene 2.0 ST array. Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed enrichment for genes involved in complement and coagulation cascades and Jak‐STAT signaling pathways. Overall, 72 genes were upregulated and 56 genes were downregulated in the postreperfusion time compared with baseline. Long pentraxin‐3, a gene and plasma protein previously associated with PGD, was the most upregulated gene (19.5‐fold increase, p = 0.04). Fibronectin leucine‐rich transmembrane protein‐3, a gene associated with cell adhesion and receptor signaling, was the most downregulated gene (4.3‐fold decrease, p = 0.04). Ischemia–reperfusion has a demonstrable impact on gene expression in visceral adipose tissue in our pilot study of nonobese, non‐PGD lung transplant recipients. Future evaluation will focus on differential adipose tissue gene expression and the development of PGD after transplant. Abstract : This study demonstrates that lung transplant reperfusion results in significant changes in thoracic visceral adipose tissue gene expression, highlighted by differences in complement and coagulation pathways and upregulation of the innate immune mediator long pentraxin‐3.